2022
DOI: 10.21203/rs.3.rs-1808138/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Soil Bunds Construction in Improving Soil Fertility In Jarso District, Western Ethiopia

Abstract: To minimize severe soil erosion ,Physical soil and water conservation practices are being implemented by community campaign, NGOs and individually by farmers in Ethiopia, because it was resulting in reduction of crop production. Hence, the objective of this study was to assess the role of physical SWC practices mainly soil bund in improving soil fertility. 18 Soil sample were taken from purposively selected four years, two years and non-conserved field. To analyze the collected data; SPSS V.21 and SAS (9.1 Ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The findings of Noorbakhsh et al (2008) also reported significant differences in available K among landscapes which increased downslope. The significantly higher K and Na were observed on plots with soil and stone-faced soil bunds and this result is consistent with the reports of Amare et al (2013) and Taye et al (2022), which clarified the accumulation of soluble bases in conserved fields.…”
Section: Effects Of Swc Interventions On Soil Biochemical Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of Noorbakhsh et al (2008) also reported significant differences in available K among landscapes which increased downslope. The significantly higher K and Na were observed on plots with soil and stone-faced soil bunds and this result is consistent with the reports of Amare et al (2013) and Taye et al (2022), which clarified the accumulation of soluble bases in conserved fields.…”
Section: Effects Of Swc Interventions On Soil Biochemical Propertiessupporting
confidence: 91%
“…The lower mean bulk density and higher total implied from higher improvement in soil organic matter after the implementation of SWCP. Siraw et al (2020) and Taye et al (2022) revealed parallel findings in conserved watersheds in Ethiopia, which were generally ascribed to reduced slope gradients, slower runoff, and improved sediment and soil organic matter settlement. These innovations have an agreement with the present study described that SWCP accumulates soil organic matter and lower bulk density.…”
Section: Effects Of Swc Interventions On Soil Physical Qualitymentioning
confidence: 66%